Risk factors for therapy failure after incision and drainage alone for perianal abscesses in children - Ding, CaiLin; Chen, YaJun; Yan, JiaYu; Wang, Kai; Tan, Sarah Siyin (Frontiers in Pediatrics, 2024)
Background: It is well known that recurrent perianal abscesses (PA) and fistula-in-ano (FIA) are the main cause of therapy failure following incision and drainage (I&D) for PA. But few studies have focused on the risk factors for therapy failure after I&D for PA in children. Risk factors for therapy failure after I&D for PA in children were retrospectively examined in a pediatric tertiary care institution.: A retrospective review of all outpatient PA children treated by I&D in Beijing Children's Hospital from January 2021 to December 2022. Follow-up was conducted in October 2023. Patients with other predisposing factors for perianal infection, such as inflammatory bowel disease, hematologic tumor and anorectal surgery, were excluded. Logistic regression yielding odds ratios (ORs) was used to assess the significance of variables for therapy failure. Results: Of 160 children initially identified, follow-up was available for 146, with a total of 172 treatments. 91 percent of children were male. The median(interquartile range)age at I&D was 2 (1, 15)months. The median follow-up duration was 20(14, 25)months. Therapy failure appeared in 25(15%) treatments for the recurrences of PA and 35(20%) treatments for the development of FIA. In univariate analysis, history of PA(P=0.001), history of I&D(P=0.014) and multilocal occurrence (P=0.003)were associated with therapy failure. The sitz bath after I&D(P=0.016) and regular cleaning of the wound after I&D(P=0.024) were associated with therapy success. In multivariate analysis, the history of PA(P=0.015,OR=3.374) and multilocal occurrence(P=0.012,OR=4.649) were independently associated with therapy failure. The regular cleaning of the wound (P=0.017,OR=0.341) and sitz bath(P=0.001,OR=0.128) after I&D were independently associated with therapy success. Conclusions: The history of PA and multilocal occurrence were predictor factors for therapy failure before I&D. Regular cleaning of the wound and sitz bath after I&D were protective factor for therapy success. Therefore, regular cleaning of the wound and sitz bath after I&D should be emphasized in all children with PA, especially in those with history of PA and multilocal occurrence.